2006
DOI: 10.1039/b511198f
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced formation of gold nanoparticles into vinyl alcohol based polymers

Abstract: Nanocomposites based on vinyl alcohol-containing polymers and nanostructured gold have been efficiently prepared by a UV photo-reduction process. The very fast process provided dispersed gold nanoparticles with average diameters ranging from 3 to 20 nm depending on the host polymer matrix and the irradiation time. Uniaxial drawing of the irradiated Au/polymer nanocomposites favours the anisotropic distribution of packed assemblies of gold particles, providing oriented films with polarization-dependent tunable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 36 publications
4
75
0
Order By: Relevance
“…PVA acted as both a reducing agent and macroscopic support for the growing silver seeds on the PLGA particle. The mechanism of photoreduction using PVA was similar to that reported elsewhere for gold reduction (38) (Fig. 10).…”
Section: Discussionsupporting
confidence: 81%
“…PVA acted as both a reducing agent and macroscopic support for the growing silver seeds on the PLGA particle. The mechanism of photoreduction using PVA was similar to that reported elsewhere for gold reduction (38) (Fig. 10).…”
Section: Discussionsupporting
confidence: 81%
“…For example Pucci et al reported the reduction of HAuCl 4 molecules adsorbed on dried vinyl alcohol-containing polymers [23].…”
Section: Resultsmentioning
confidence: 99%
“…The UV-vis absorption spectrum of chitosan/ AuNPs nanocomposite exhibited characteristic SPR peak at 542 nm [18]. In addition, Pucci et al [19] synthesized AuNPs using poly (vinyl) alcohol (PVA) under UV irradiation with different time duration and found that the AuNPs showed characteristic SPR band at 550 nm. As can be seen in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…These results are in good agreement with those reported by Huang and Yang [14], and Jin et al [17] for chitosan/AuNPs nanocomposites. Pucci et al [19] also found that TEM images of PVA-stabilized AuNPs showed spherical shape of nanoparticles with average size of 3-20 nm. The presence of elemental gold in the formed nanoparticles was examined by energy dispersive X-ray (EDX) analysis.…”
Section: Tem and Edx Analysismentioning
confidence: 95%